A Methodological Approach to Revealing the Landscape Morphology of Heijing Village Using Fractal Theory - Peiyuan Li; Shanshan Liu; Pengjun Wu; Yao Liu (Buildings, 2025)
With the ongoing globalization, traditional villages around the world face the challenge of balancing modernization with the preservation of their cultural and spatial integrity. Heijing Village, a representative traditional settlement in Yunnan, showcases this global phenomenon through its distinctive spatial form and rich multi-ethnic cultural heritage. This study examines the landscape morphology of Heijing Village to reveal its spatial organization, cultural significance, and adaptive evolution. By applying fractal theory, we quantify the spatial complexity and self-similarity of the village, uncovering underlying patterns in land use that contribute to its sustainability and historical continuity. This study’s innovation lies in its use of fractal analysis to assess the village’s dynamic landscape, offering a novel method for understanding the interplay between traditional spaces and modern demands. The findings demonstrate variations in fractal dimension values before and after model optimization, indicating an enhanced ability to capture the intricate spatial structure of Heijing Village. Notably, changes in fractal dimensions across different land use types (e.g., residential areas: 1.4751 to 1.5323 and public service areas: 1.2846 to 1.3453) suggest improvements in quantification accuracy rather than actual physical transformations. This refined methodological framework provides a robust and replicable tool for planners to quantitatively assess the morphological characteristics of traditional settlements, supporting more evidence-based conservation strategies.